Inception and Magnitude of Subsurface Evaporation for a Bare Soil with Natural Surface Boundary Conditions. Issue 5 (29th August 2014) - Deol, Pukhraj K.; Heitman, Joshua L.; Amoozegar, Aziz; Ren, Tusheng; Horton, Robert
Abstract : A dry surface layer (DSL) forms when wet soil is exposed to the sun; development of a DSL coincides with a shift between surface and subsurface evaporation. There remains debate as to when this shift from surface to subsurface evaporation occurs relative to the timing of the shift between potential and falling‐rate evaporation. We performed a field experiment to investigate the onset of subsurface evaporation, development of the DSL, and the extent of the evaporation zone. Our objective was to determine the timing of the onset of subsurface evaporation with respect to decline in evaporation rates. We estimated total (surface plus subsurface) and subsurface soil evaporation rates using microlysimeter (water mass balance) and sensible heat balance (SHB) approaches, respectively, for a bare loamy sand soil under natural wetting and drying cycles. Results showed that the onset of subsurface evaporation coincided with the beginning of falling‐rate evaporation. The evaporation zone extended into the subsurface when evaporation rates fell below the potential rate but were still as high as 50% of potential evaporation. Over a 5‐d drying event, estimated evaporation zones were as deep as 4 to 9 mm, and the estimated DSL had a maximum depth of approximately 6 mm. A low soil water content‐dependent albedo was observed when evaporation occurred at potential rates, but albedo increased as evaporation rates declined. Data from the intensive observation period suggest that this increase in albedo corresponded to formation of a DSL and onset of subsurface evaporation. Overall, surface drying and formation of a DSL appeared to be a dominant process for this coarse‐texture soil exposed to ambient boundary conditions, even as evaporation rates remained relatively high (0.3 mm h −1 ).